n → ∞ lim n 1 k = 0 ∑ n − 1 cos ( 2 n k π ) = b π a
a and b are coprime positive integers satisfying the equation above. Find a + b .
Notation: ⌊ ⋅ ⌋ denotes the floor function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
lim n → ∞ n 1 ∑ k = 0 n − 1 cos ( 2 n k π )
= π 2 lim n → ∞ π 2 n 1 ∑ k = 0 n − 1 cos ( 2 n k π )
= π 2 ∫ a b cos x d x
[Where a = lim n → ∞ π 2 n 0 , b = lim n → ∞ π 2 n ( n − 1 ) , x = π 2 n k , d x = π 2 n 1 ]
= π 2 sin 2 π = π 2
Thank you for editing
You should have set the answer as b π a . Then find a + b . Note also that n is used on the left-hand side.
Log in to reply
Thanks. I see that this problem has been edited.
As a moderator, please do not edit problem significantly, because that doesn't update it for other who already answered the problem. Instead, simply report the problem and staff will handle it delicately.
Thanks for helping us make Brilliant better :)
This is still not correct! Why can't p = 3 , χ = 2 3 π ⇒ p + ⌊ χ ⌋ = 7 be the answer? Staffs, please look into this again!
Log in to reply
Thanks for bringing this to our attention.
I've updated the problem statement and the answer.
I have amended the problem for you.
Problem Loading...
Note Loading...
Set Loading...
L = n → ∞ lim n 1 k = 0 ∑ n − 1 cos ( 2 n k π ) = ∫ 0 1 cos ( 2 π x ) d x = π 2 sin ( 2 π x ) ∣ ∣ ∣ ∣ 0 1 = π 2 By Riemann’s sum: n → ∞ lim n 1 k = 1 ∑ n f ( n k ) = ∫ a b f ( x ) d x a = n → ∞ lim n 0 = 0 , b = n → ∞ lim n n − 1 = 1
⟹ a + b = 2 + 1 = 3